"It's not just sexy pics": An investigation into sexting behaviour and behavioural problems in adolescents. (April 2021) - Foody, Mairéad; Mazzone, Angela; Laffan, Derek Alan; Loftsson, Magnus; O'Higgins Norman, James
Abstract: Sexting has been identified as an emerging online phenomenon among adolescents. However, research investigating its behavioural correlates and the sexting behaviours (i.e., sending and/or receiving) is still scarce. The present study investigated the association between different sexting behaviours and various behavioural problems among Irish adolescents. A sample of 848 students aged 15–18 participated in the study (Mage = 16.4 years). A self-report measure assessing the sharing of sexual images among teenagers was created and administered for the purpose of this study. The Strengths and Difficulties Questionnaire was adopted to detect emotional and behavioural problems. Findings showed that senders of sexts are more likely to be girls, whereas receivers are more likely to be boys. Two-way sexting (i.e., sending and receiving sexts) was more prominent among boys, LGBTQ adolescents, and positively associated with peer problems. Findings are discussed in terms of their theoretical and practical relevance. Highlights: Distinct sexting behaviours have been investigated in a sample of Irish adolescents Girls tend to send sexts, whereas boys tend to both send and receive sexts Two-way sexters show more behavioural problems compared to non-involved adolescents LGBTQ adolescents might engage in two-way sexting to explore sexuality issues